Don't breathe the air : air pollution and U.S. environmental politics, 1945-1970 - Dewey, Scott Hamilton (Environmental history series, 2000)
"In Don't Breathe the Air, Scott Hamilton Dewey traces the history of air pollution control efforts, focusing on the decade of the sixties, and describes how local efforts helped create both the modern environmental movement and federal environmental policy."--Jacket